1982
DOI: 10.3758/bf03202776
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous musical figures and auditory streaming

Abstract: Three experiments with musicians and nonmusicians (N=338) explored variations of Deutsch's musical scale illusion. Conditions under which the illusion occurs were elucidated and data obtained which supported Bregman's suggestion that auditory streaming results from a competition among alternative perceptual organizations. In Experiment 1, a series of studies showed that it is more difficult to induce the scale illusion than might be expected if it is accepted that an illusion will be present for most observers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Experiment 2 included no NS note pattern, and it provided listeners with a closed set of (written) responses (cf. Smith et al, 1982). The closed set is well justified by the finding in Experiment 1 that 90% of all responses fell into two categories ("arc" and "linear") and that only a small portion fell into the "other" category.…”
Section: Data Treatmentmentioning
confidence: 62%
See 2 more Smart Citations
“…Experiment 2 included no NS note pattern, and it provided listeners with a closed set of (written) responses (cf. Smith et al, 1982). The closed set is well justified by the finding in Experiment 1 that 90% of all responses fell into two categories ("arc" and "linear") and that only a small portion fell into the "other" category.…”
Section: Data Treatmentmentioning
confidence: 62%
“…However, there are some considerations that caution against such an interpretation. The presence of a substantial number of veridical responses in a closed set is not an unique finding (see Smith et al, 1982). The scale illusion, while compelling, is not completely convincing.…”
Section: +1mentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy percent of her subjects reported hearing the percept shown in Figure 5c; that is, they reported a "wave" pattern percept in which pitch information took precedence over all else, attributing all the high notes to the right ear and all the low notes to the left ear. Smith, Hausfeld, Power, and Gorta (1982) discovered that replication of Deutsch's findings occurred only when subjects' choices of percepts were limited to the possibilities presented in Figure 5. Moreover, they discovered that musicians were more likely than nonmusicians to report streaming by pitch (suggesting that Deutsch's subjects may have had musical training), and that, when additional information (timbre, loudness, and tune) was given, this was used by subjects so that pitch became only one of many possible cues to correct streaming.…”
mentioning
confidence: 86%
“…Two ofthe findings of Smith et al (1982) have led to the present experiment: first, they reported that their subjects (particularly musicians) considered the veridical percept ( Figure 5a) to be a most unlikely tune, and second, they suggested that the musicians' tendency to not report the scale percept ( Figure 5b) might have been because they considered this percept a less typical tune than the wave pattern ( Figure 5c) (Smith et aI., 1982, p. 463). In other words, neither the veridical percept nor the scale percept was expected by subjects, which brings us again to the consideration of the baroque technique of presenting tunes separately before interleaving them.…”
mentioning
confidence: 99%